Towards a multi-marker prognostic strategy in acute heart failure: a role for GDF-15 - Bettencourt, Paulo (2018)
AIMS: Growth differentiation factor (GDF)-15 mirrors inflammation and oxidative stress in cardiovascular diseases. Brain natriuretic peptide (BNP) is associated with cardiomyocyte stretch in heart failure (HF). The objective of this study was to evaluate the prognostic impact of plasma GDF-15 and BNP in acute HF. METHODS AND RESULTS: We studied a subgroup of patients prospectively recruited in an acute HF registry (follow-up: 2 years; endpoint: all-cause mortality). Cox regression multivariate models were built to study the association of GDF-15 and mortality. Further cross-classification according to discharge GDF-15 (mean) and BNP (mean) and association with mortality was studied. We studied 158 patients: seventy-nine were male, mean age was 75 years, 55.1% had left ventricular ejection fraction < 40%, mean discharge BNP was 1000 pg/mL, and mean GDF-15 was 3013 ng/mL. Higher BNP and GDF-15 predicted 2-year mortality. Patients with GDF-15 ≥ 3000 ng/mL had a multivariate adjusted 2-year death risk of 1.86 (1.08-3.18). Patients discharged with both BNP and GDF-15 above the mean had an adjusted hazard ratio of 4.33 (2.07-9.06) when compared with those with both <mean. CONCLUSIONS: Higher GDF-15 associated with worse prognosis in acute HF independently of BNP. When both biomarkers GDF-15 and BNP were elevated at discharge, the 2-year mortality risk increased over four-fold. Biomarkers related to different pathophysiological pathways can provide incremental prognostic information in acute HF.